Halal Industry and Islamic Banking: A Study of Halal Ecosystem Regulation in Indonesia - Muhammad Khozin Ahyar; Muhammad Yusuf Perkasa Wibowo (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This article aims to analyze the halal industry lately is developing rapidly throughout the needs of the community. Indonesia is one of the world's largest halal product markets because it has favourable demographic conditions. Regulations on the submission of halal products in Indonesia itself have not led to the use of Islamic financial institutions in terms of the certification assessment. Even though the Qur'an and the hadith have explained that in doing business, how to get capital must also come from halal sources. This study uses a qualitative method by conducting a literature review on related references. The author found that the JPH Law (Halal Product Guarantee), and the halal certification requirements of LPPOM MUI, have not included finance as one requirement or assessment indicators in halal product certification. Financial indicators should be able to be one indicator in the certification of halal products because finance is one of the initial sources (upstream / input) of the creation of halal products.